Cadastre 2014 and beyond - Steudler, D. (FIG, 2020)
Report introduces about The Cadastre 2014 journey; review and impact of the six statements of Cadastre 2014; developments out of Cadastre 2014 internationally and in switzerland in particular ; case studies from newly renovated land administration systems in the emerging economies; a case study from South Korea; LADM and its role in establishing cadastral systems; from CADASTRE to land governance.